Soluble PD-L1 Expression After Intravenous Treatment of Cancer Patients With Selenite in Phase I Clinical Trial - Razaghi, Ali; Mansouri, Ladan; Brodin, Ola; Björnstedt, Mikael; Lundahl, Joachim (Frontiers in Oncology, 2022)
A high expression level of programmed death-ligand 1 (PD-L1) is observed in different types of cancers (particularly lung cancer). Soluble (s)PD-L1 may be used as a prognostic marker and a target for anti-cancer immunity, as well as, predicting gene therapy or systemic immunotherapy in blocking the PD-1 and PD-L1 checkpoint. Studies that evaluate the effects of the immune regulator selenium on PD-L1 expression show ambiguous results. Thus, we aimed to analyze sPD-L1 levels in samples from patients who underwent different dosages of selenite treatment in phase I clinical trial. We hypothesized that selenite modulates the sPD-L1 levels in the plasma as a consequence of the suggested mode of action of selenotherapy in cancer patients. In conclusion, our results support the view that selenotherapy does not substantially affect the PD-1/PD-L1 axis judged by sPD-L1 analysis. Furthermore, no significant correlation was observed between the survival and sPD-L1 expression nor sPD-L1 changes. However, due to a dynamic individual sPD-L1 profile and a high variation in survival, we suggest that further studies are needed to identify whether individual patients can be benefited from combinational seleno- and anti-PD-L1 therapy.